2017
DOI: 10.1007/978-3-319-58771-4_25
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Reconstruction and Segmentation of CT Scans with Shadowed Data

Abstract: We propose a variational approach for simultaneous reconstruction and multiclass segmentation of X-ray CT images, with limited field of view and missing data. We propose a simple energy minimisation approach, loosely based on a Bayesian rationale. The resulting non convex problem is solved by alternating reconstruction steps using an iterated relaxed proximal gradient, and a proximal approach for the segmentation. Preliminary results on synthetic data demonstrate the potential of the approach for synchrotron i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Image segmentation and 3D-reconstruction may appear as two disconnected problems. Nevertheless, each task contributes information which may be interesting for the other, and the joint solving of these inverse problems has proven valuable, for instance, in the context of dense multiview reconstruction [7], X-ray tomography [9], pose estimation [18], SLAM [25] or hyperspectral imaging [28]. Inspired by such joint approaches to simultaneous reconstruction and segmentation, in the rest of this work we revisit the photometric stereo problem in the case where no prior segmentation of the object has been performed i.e., domain Ω in (1) is unknown.…”
Section: Variational Methods For Photometric Stereo and Segmentationmentioning
confidence: 99%
“…Image segmentation and 3D-reconstruction may appear as two disconnected problems. Nevertheless, each task contributes information which may be interesting for the other, and the joint solving of these inverse problems has proven valuable, for instance, in the context of dense multiview reconstruction [7], X-ray tomography [9], pose estimation [18], SLAM [25] or hyperspectral imaging [28]. Inspired by such joint approaches to simultaneous reconstruction and segmentation, in the rest of this work we revisit the photometric stereo problem in the case where no prior segmentation of the object has been performed i.e., domain Ω in (1) is unknown.…”
Section: Variational Methods For Photometric Stereo and Segmentationmentioning
confidence: 99%
“…This splitting turns the problem into two simple problems solved by the conjugate gradient method and a submodular minimization solver. In [9] the authors suggested a joint reconstruction and segmentation method in a variational framework. Other techniques include graph cut [10], [11] and convex relaxation techniques [12].…”
Section: A Related Workmentioning
confidence: 99%
“…SPECT), or the segmentation term. In [31,32,34] the authors model the segmentation as a mixture of Gaussian distribution, while [30] has a a region-based segmentation approach similar to what we propose. However, [30] penalises the squared 2-norm of segmentation, imposing spatial smoothness.…”
Section: Comparison To Other Joint Reconstruction and Segmentation Apmentioning
confidence: 99%
“…In [31,32,34] the authors model the segmentation as a mixture of Gaussian distribution, while [30] has a a region-based segmentation approach similar to what we propose. However, [30] penalises the squared 2-norm of segmentation, imposing spatial smoothness. In our proposed joint approach, we perform reconstruction and segmentation in a unified Bregman iteration scheme, exploiting the advantage of improving the reconstruction, which results in a more accurate segmentation.…”
Section: Comparison To Other Joint Reconstruction and Segmentation Apmentioning
confidence: 99%